Application of Portable Raman Spectrometers for Rapid Production Control and Analysis in the Field Environment - Voyevoda, V.M.; Melenevskyi, D.O.; Derzhypolskyi, A.G. (Science and Innovation, 2024)
The fundamental theory of Raman spectroscopy and its application in various fields have been described. Thermo Fіsher Scіentіfіc Corporation, a world leader in high-tech instruments, has designed a series of portable Raman spectrometers for a broad scope of application.